Review on Small Horizontal-Axis Wind Turbines - Ismail, Kamal A. R.; Lino, Fatima A. M.; de Almeida, Odenir; Teggar, Mohamed; Scalon, Vicente Luiz [UNESP]; Okita, Willian M. (Springer Nature, 2024)
Wind energy generation is continuously expanding in the global energy scenario of sustainable resources to replace fossil energy and alleviate the negative impacts on the environment. With the global attention focused on centralized generation, less attention has been paid to improving small wind turbines. As a result, small wind turbines have marginal contribution to the global energy scenarios, because of their poor performance and high cost. This review is aimed to gather methodologies and experiences in big machines and avail them for small machines. The review presents an evaluation of global expansion of wind energy followed by investigations on the blade element momentum (BEM), lifting line-based methods and other vorticity-based models, wind turbine noise, optimization of airfoils, blades and rotors, and commercial numerical codes with a special focus on small wind turbines. The main findings of the review show the necessity of more research and development efforts to improve the performance of small wind turbines and acceptability by the users, integration of the BEM with lifting line methods and other available software, more numerical and experimental real-scale studies on noise generation and its impact on the neighboring living beings, development of new optimized airfoils and blades for low Reynolds number operation and urban wind profile, and creation of computational codes for the design, micrositing, and simulation of small wind turbines. It is hoped that this review can be of help to researchers, development engineers, young scientists, and general readers interested in the topic.
Keywords: Aerodynamic noise; Airfoils Optimization; BEM; Blades for low wind speeds; Lifting line methods; Small wind turbines